Dealership e-Commerce package (Online inventory control system) / Hew Suh Jeng - Hew , Suh Jeng (2003)
e-Commerce business becomes very popular between the medium and large retailing companies in Malaysia. Some small companies face some problems like the cost and lack of computer knowledge when they consider venturing into Internet business. For my thesis. I have developed a Dealership E-commerce Package (DECP) that can overcome all these problems. I will focus on the part of Online Inventory Control System (OICS). DECP is free package provided by the supplier to the dealers. This give benefits to the dealers especially for those who cannot afford to have their own web sites. OICS is an efficient system for dealers to manage their inventories online. OICS consists of two major sections: administrator section and user section. Administrator section consists of 6 modules: Authentication module, Category Management. Product Management, Stock Management, Purchase Order and Manufacturer Address Book User sections consist of Online Product Catalog. In order to develop my OICS in short time und low cost. I have chosen some efficient tools in developing my system Tools thnt I used include Windows 2000. PHP4, Apache. MySQL. Edit Plus, Microsoft Internet Explorer, and Macromedia Dreamweaver Java Script and Adobe Photoshop 6.0. Since I have experience in using PHP and My SQL during my industrial training. I feel confident and comfortable to usethese tools. DECP is still a new concept in Malaysia. Therefore, in my opinions, OICS of DECP is a potential system for local dealers to maximize their business profits through Internet. This can enhance and increase Malaysia's economic strength.